EVALUATING THE EFFECTIVENESS OF KERN’S SIX-STEP CURRICULUM DEVELOPMENT IN RESPIRATORY THERAPY EDUCATION - AMMAR BAALKHIR, AHMED ALMUTAIRI, HAMOUD ALOTAIBI, IBRAHIM ALANSARI, MOHAMMED HUSSAIN, NAJDIA BARAKAT; DANIYAH SAATI, MAWADDAH HUSSAIN, GHARAM ZAGZOOG, AISHA KHALIFA, ABEER SINDI, HADEEL SAUD (TPM – Testing, Psychometrics, Methodology in Applied Psychology, 2025)
Background: Respiratory Therapy (RT) education at high-acuity centers like King Abdullah Medical City (KAMC) often lacks systematic design, limiting staff competency in advanced skills essential for managing critical respiratory conditions such as ARDS. Objective: To evaluate the effectiveness of a comprehensive RT training course developed using Kern’s Six-Step Curriculum Development model in improving knowledge, clinical skills, and confidence among RT staff at KAMC. Methods: A cross-sectional, pre-post intervention design was used involving 40 RT staff. Needs assessment identified knowledge gaps. The curriculum combined lectures, case discussions, high-fidelity simulation, and technology-assisted ventilator practice. Knowledge (MCQ), clinical skills (OSCE), and participant satisfaction were measured before and after the course. Statistical analysis included paired t-tests and thematic analysis of qualitative feedback. Results: Post-course MCQ scores showed a significant 62.55% mean improvement (p < 0.001). Clinical skills assessments demonstrated a 100% success rate across simulation stations. Participant surveys indicated high satisfaction, increased confidence, and perceived applicability in clinical practice. Conclusion: Kern’s Six-Step Model provides a structured, effective framework for RT education, enhancing theoretical knowledge, clinical competencies, and staff confidence. Simulation-based training is key for translating knowledge into practice. This approach supports ongoing, equitable professional development in critical care respiratory therapy settings.